Legal Issues in Implementing E-Commerce in GCC Countries from the Perspective of Financial Managers - Omar Masood; Kiran Javaria (Jurnal Hukum Novelty, 2021)
Introduction to The Problem: This study explains the concept of legal risk in marketing in e-commerce world as there is currently insufficient research studies on the concept despite its critical importance in influencing the behaviour of consumers.Purpose/Objective Study: The problem statement/purpose of study is to explain that what are the different barriers faced by financial managers during an uncertain and legal risky situation.Design/Methodology/Approach: The study utilizes both primary and secondary data from Gulf Cooperation Council (GCC) countries in order to get reliable results. There are different risk factors that affect the purchasing behaviour of consumers who shop online. The consumer’s perception of risk may be the result of all the emotional processes through which consumers recognize, organize and provide meaning to sensations received, such as the need for product quality, safety online and overall satisfaction. The primary data consists of a survey of online shoppers. The research data and questionnaire were administered to 972 GCC internet users who are classed as experienced and avid users. The secondary data includes an analysis of the various theories of consumer behaviour, models of online adoption, legal risk factors to marketing and shopping online, models of the adoption of innovation and new ways of marketing and trade. Both techniques are utilized to examine the relationship between perceived risk strategies and customer satisfaction as well as examined the customer involvement and propensity to take risk on existing relation of online shopping.Findings: According to study results, legal risk is very important in GCC countries which ultimately influence the customer involvement, satisfaction and purchasing behaviour. GCC countries should attempts to create a coherent legal and regulatory framework (like Lessons can be learnt from the EU). It will help to reduce the legal risk and remove the obstacles to the growth of e-commerce in GCC countries by affirming a certain level of transparency by imposing prior information requirements for electronic contracts, as well as regulating commercial communication and advertisements and regulating consumers' technical errors.Paper Type: Research Article